Diffusion weighted imaging of prefrontal cortex in prodromal huntington's disease. Issue 4 (9th April 2013) - Matsui, Joy T.; Vaidya, Jatin G.; Johnson, Hans J.; Magnotta, Vincent A.; Long, Jeffrey D.; Mills, James A.; Lowe, Mark J.; Sakaie, Ken E.; Rao, Stephen M.; Smith, Megan M.; Paulsen, Jane S.
<x xml:space="preserve">Abstract</x> Huntington's disease (HD) is a devastating neurodegenerative disease with no effective disease‐modifying treatments. There is considerable interest in finding reliable indicators of disease progression to judge the efficacy of novel treatments that slow or stop disease onset before debilitating signs appear. Diffusion‐weighted imaging (DWI) may provide a reliable marker of disease progression by characterizing diffusivity changes in white matter (WM) in individuals with prodromal HD. The prefrontal cortex (PFC) may play a role in HD progression due to its prominent striatal connections and documented role in executive function. This study uses DWI to characterize diffusivity in specific regions of PFC WM defined by FreeSurfer in 53 prodromal HD participants and 34 controls. Prodromal HD individuals were separated into three CAG‐Age Product (CAP) groups (16 low, 22 medium, 15 high) that indexed baseline progression. Statistically significant increases in mean diffusivity (MD) and radial diffusivity (RD) among CAP groups relative to controls were seen in inferior and lateral PFC regions. For MD and RD, differences among controls and HD participants tracked with baseline disease progression. The smallest difference was for the low group and the largest for the high group. Significant correlations between Trail Making Test B (TMTB) and mean fractional anisotropy (FA) and/or RD paralleled group differences in mean MD and/or RD in several right hemisphere regions. The gradient of effects that tracked with CAP group suggests DWI may provide markers of disease progression in future longitudinal studies as increasing diffusivity abnormalities in the lateral PFC of prodromal HD individuals. Hum Brain Mapp 35:1562–1573, 2014. © 2013 Wiley Periodicals, Inc.